Modeling and Performance Analysis of Simplified Two-Diode Model of Photovoltaic Cells - Prakash, Saripalli Bhanu; Singh, Gagan; Singh, Sonika (Frontiers in Physics, 2021)
For a quick and consistent photovoltaic (PV) module design, an effective, fast and exact simulator is crucial to examine the performance of the photovoltaic cell under partial or quick variation of temperature and irradiance. The most prevalent modelling strategy is to apply equivalent (electrical) circuit that encompasses together non-linear and linear mechanisms. This work proposes the modeling and analysis for four parameter two-diode photovoltaic cell model based on manufacturer’s data-sheet. The proposed model need only four parameters compared to previous developed seven parameter two-diode model to reduce the computational complexity. To develop a specific model of photovoltaic cell, the fundamental requirement is the data of temperature and irradiance. The variation of these variables totally affects the output constraints like current, voltage and power. Thus, it is substantial to design a precise model of the photovoltaic cell module with reduced computation period. The Two-diode photovoltaic module with four constraints which is identified to be more accurate and have improved performance compared to one-diode model particularly at lower irradiance. To confirm the accurateness of proposed model the method is applied on two different photovoltaic modules. The proposed model and modeling method are helpful for power electronic designers who requires the fast, accurate, simple and easy to implement method for use in photovoltaic system simulation. The electrical equivalent circuit and standard equations of photovoltaic cell are analyzed and the proposed two-diode model is simulated by using MATLAB/Simulink software and validated for poly-crystalline and mono-crystalline solar cell under standard test conditions.